Importance of Cultivating Emotional Intelligence in Children (Sains Humanika, 2014)
Educating children in the present age is not easy. Various challenges and disturbances to be encountered. Educating children not only with only enough food, clothes and education. The emphasis is only concerned with the aspect of intellectual intelligence regardless of their feelings will leave a negative impact on the emotional development of children (Poh Siew Boon, 2001). According to Boon Siew Boon (2001), elements of emotional intelligence should be taught to children as the world now has a complex change in patterns of human social relations that much negative influence that can be seen through the mass media and television. This causes children present irritability and aggressive due to change this phenomenon. This paper will discuss the conceptual concept of emotional intelligence instilled in preschool children. This paper also discusses the problems faced by pre-school teachers in the implementation of teaching and learning practices of emotional intelligence preschoolers. Limitations of teaching aids (BBM) in teaching and learning elements of emotional intelligence in the preschool lead teachers teaching hard to deliver this element to a child. Finally, teachers are making element of emotional intelligence as a side subject only infused with any other subject that are important in the learning process. This shows lack of emotional intelligence elements emphasized by pre-school teachers in the teaching and learning of children. In fact, this element is very important in the development and formation of a stable of kid emotional. It is important to produce individuals who can and are able to control and manage emotions well and be able to avoid the temptations of the things that should not be a result of failure to control his emotions when faced with the pressures experienced in life (Saarni, 1999).
Keywords: Emotional intelligent; preschooler